2003
DOI: 10.1016/s0266-7681(03)00014-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Splinting After Extensor Tendon Repair in Zones V to VII

Abstract: This retrospective study evaluates a dynamic active motion protocol for extensor tendon repairs in zones V to VII. Fifty-eight patients with 87 extensor tendon injuries were examined. Using Geldmacher's and Kleinert and Verdan's evaluation systems, the results were graded as "excellent" and "good" in more than 94%, and as "satisfactory" in the remainder. The need for secondary tenolysis was low (6%), and no other surgical complication occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Subsequently, many authors retrospectively demonstrated successful outcomes using these protocols. 7,11,12,20 More recently, several studies have prospectively investigated the differences between static immobilization, early dynamic mobilization, and early active mobilization protocols.…”
Section: Rehabilitationmentioning
confidence: 99%
“…Subsequently, many authors retrospectively demonstrated successful outcomes using these protocols. 7,11,12,20 More recently, several studies have prospectively investigated the differences between static immobilization, early dynamic mobilization, and early active mobilization protocols.…”
Section: Rehabilitationmentioning
confidence: 99%
“…9 Chow et al 10 showed in a case-control study that 60% of the group treated with static splints suffered a measure of extensor lag or lack of flexion, whereas all patients treated with DESs had no extensor lag or loss of flexion. Other groups [11][12][13][14] have also obtained good results with the DES without clinically significant complications or repair rupture or gapping. The DES has major disadvantages, however; its construction is expensive and time consuming for therapists and patients.…”
mentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8][9][10] Whereas the initial formation of scar between tendon ends provides physical continuity at the site of disruption, proliferation of scar between the tendon and adjacent tissues is undesirable because these attachments can impede the gliding mechanism of the tendon, whether sheathed or not. 11 The majority of research in the area of flexor and extensor tendon repair in the hand has focused on the development of improved suture repair techniques and the enhancement of postoperative rehabilitation protocols allowing early motion.…”
mentioning
confidence: 99%
“…11 The majority of research in the area of flexor and extensor tendon repair in the hand has focused on the development of improved suture repair techniques and the enhancement of postoperative rehabilitation protocols allowing early motion. 4,5,[12][13][14][15][16][17][18][19][20][21][22][23] These improved surgical and rehabilitation methods have led to better clinical outcomes, but scarring and adhesion formation remain important complications. 1,2 Even with the best surgical techniques and the optimal therapeutic protocols, results can be unpredictable.…”
mentioning
confidence: 99%